PENCARIAN JALUR ALTERNATIF PADA DAERAH BENCANA LUMPUR SIDOARJO DENGAN METODE ANALYTIC HIERARCHY PROCESS BERBASIS WAP - Arna Fariza; Afrida Helen; Ardinur Mahyuzar (Universitas Ahmad Dahlan, 2009)
In line with the increasing interest on Lapindo mud disaster which causes several roadway covered by mud, there is a need to give an alternative solution for traffic transportation problem in surrounding area. The possible criteria for the solution of this road way are length, surface, traffic, and width of the road. Types of vehicle across the road also give a contribution to the criteria. By using Geography Information System (GIS), it is easy to all drivers to take decision which way has to be chosen based on the real condition. GIS is used to visualize the alternative road, which is possible to take. Analytic Hierarchy Processing (AHP) is a decision method which is based on many criteria and alternatives. The input of AHP can be a preference or real value. Applied AHP to decide value of each alternative is based on application of Wireless Application Protocol (WAP) assessment.